Interdependence of Science and Social Context Through Lens of Banjar Culture Activities (Batimung): Convergent Model - Almubarak, Almubarak; Sriyati, Siti; Liliawati, Winny (Universitas Lambung Mangkurat, 2024)
The integration of culture into science education serves as a bridge of knowledge, ensuring that students develop a comprehensive understanding of the scientific and social context and possess literacy as potential educators. The research objectives are to determine the following: 1) the topics that students are most interested in discussing in the context of